Effects of Gut Bacteria on the Fitness of Rice Leaf Folder Cnaphalocrocis medinalis - Qinjian Pan; Qingpeng Wang; Ikkei Shikano; Fang Liu; Zhichao Yao (Insects)
The rice leaf folder Cnaphalocrocis medinalis is an important migratory pest in Asia. Although this pest possesses diverse bacterial communities in its gut, functions of these bacteria in modulating host fitness, including development durations, pupal weight, adult longevity, and fecundity, remain unknown. We isolated gut bacteria from field–collected C. medinalis larvae using a culture–dependent method and identified 15 bacterial isolates. Six of the isolates (Klebsiella aerogenes, Klebsiella pneumoniae, Enterobacter ludwigii, Enterobacter asburiae, Pantoea dispersa, and Pantoea ananatis) were newly discovered in C. medinalis. When larvae were orally inoculated with individual bacterial isolates, 15 isolates showed varying degrees of effects on C. medinalis fitness. Importantly, we found that 10 bacterial isolates induced significant larval mortality. Specifically, the inoculation of Pseudomonas mosselii, P. dispersa, Chryseobacterium culicis, P. ananatis, and Myroides odoratus caused high mortality ranging from 40.0% to 56.7%. However, reducing the entire gut bacterial community with antibiotic treatment negatively impacted C. medinalis fitness, while the reinoculation of a bacterial community to antibiotic–treated larvae recovered some of the adverse effects. In particular, control and bacterial community–inoculated C. medinalis laid approximately 37.6% more eggs than antibiotic–treated C. medinalis. This suggests that these bacteria affect their hosts differently when they are together as compared to alone. Our results reveal that C. medinalis harbors gut bacteria capable of both mutualistic and pathogenic interactions, suggesting their potential as biocontrol agents and indicating that targeting the gut bacterial community could be an effective strategy for controlling C. medinalis infestations.